Epigenetic Effects on Pediatric Traumatic Brain Injury Recovery (EETR): An Observational, Prospective, Longitudinal Concurrent Cohort Study Protocol - Treble-Barna, Amery; Patronick, Jamie; Uchani, Srivatsan; Marousis, Noelle C.; Zigler, Christina K.; Fink, Ericka L.; Kochanek, Patrick M.; Conley, Yvette P.; Yeates, Keith Owen (Frontiers in Neurology, 2020)
Introduction: Unexplained heterogeneity in outcomes following pediatric traumatic brain injury (TBI) is one of the most critical barriers to the development of effective prognostic tools and therapeutics. The addition of personal biological factors to our prediction models may account for a significant portion of unexplained variance and advance the field towards precision rehabilitation medicine. The overarching goal of the Epigenetic Effects on Pediatric Traumatic Brain Injury Recovery (EETR) study is to investigate an epigenetic biomarker involved in both childhood adversity and post-injury neuroplasticity to better understand heterogeneity in neurobehavioral outcomes following pediatric TBI. Our primary hypothesis is that childhood adversity will be associated with worse neurobehavioral recovery in part through an epigenetically mediated reduction in brain-derived neurotrophic factor (BDNF) expression in response to TBI. Methods and analysis: EETR is an observational, prospective, longitudinal concurrent cohort study of children aged 3-18 years with either TBI (n=200) or orthopedic injury (n=100), recruited from the UPMC Children’s Hospital of Pittsburgh. Participants complete study visits acutely and at 6- and 12-months post-injury. Blood and saliva biosamples are collected at all time points—and CSF when available acutely—for epigenetic and proteomic analysis of BDNF. Additional measures assess injury characteristics, pre- and post-injury child neurobehavioral functioning, childhood adversity, and potential covariates/confounders. Recruitment began in July 2017 and will occur for approximately 6 years, with data collection complete by mid-2023. Analyses will characterize BDNF DNA methylation and protein levels over the recovery period and investigate this novel biomarker as a potential biological mechanism underlying the known association between childhood adversity and worse neurobehavioral outcomes following pediatric TBI. Ethics and dissemination: The study received ethics approval from the University of Pittsburgh Institutional Review Board. Participants and their parents provide informed consent/assent. Research findings will be disseminated via local and international conference presentations and manuscripts submitted to peer-reviewed journals. Trial Registration: The study is registered with clinicaltrials.org (ClinicalTrials.gov Identifier: NCT04186429).